Changes in the incidence of acute gonococcal and nongonococcal salpingitis. A five-year study from an urban area of central Sweden. Issue 4 (August 1978) - Forslin, L; Falk, V; Danielsson, D
Abstract : The incidence of acute gonococcal and nongonococcal salpingitis for a five-year-period (1970--74) was studied retrospectively in an urban area of central Sweden. The investigation was undertaken to see if the reported decrease of gonorrhoea in Sweden had been followed by a change in the incidence of gonococcal salpingitis--the most common complication of gonorrhoea. The study showed that the relative incidence of acute gonococcal salpingitis had decreased even more than urogenital gonorrhoea and these findings thus indicate a real decrease of gonorrhoea. At the same time there were more patients with nongonococcal salpingitis. During the period of the study the gonococcal complement-fixation test (GCFT) gave positive results in 40% to 80% of the patients with gonococcal salpingitis. The yield with this test was only 4% in patients with nongonococcal salpingitis during 1970 but it increased successively and was 23% in 1974. This increase was statistically highly significant (P less than 0.001).